Evaluation of the educational programme for caregivers of the elderly in Windhoek and Rehoboth, Namibia - Kloppers, Joan.M; Pretorius, Louise; Kloppers, Alfreda R. E. (International Journal of Medicine, 2015)
There are many reasons why the elderly may be in need of care, for example, if an elderly person suffers a medical illness, such as a stroke or a diagnosis of dementia or Alzheimer's disease, he/she may need assistance and care (Boehlke, 2001).Another major problem for elderly people is the prevalence of co-morbidity (several chronic diseases in one person) which makes treatment and quality of care and life more difficult. In many instances care for the frail elderly, especially in long-term care institutions, is provided under minimal supervision by caregivers who lay people. This can lead to poor-quality care or neglect of the frail elderly. Clarke (2008) stated that the role of the caregiver involves the application to the principles of caring at any level of care. A qualitative, explorative, descriptive, contextual and phenomenology design was used to perform this study.The purpose of this study was to develop, implement and evaluate a supportive educational programme for caregivers of the elderly in old-age homes in Windhoek.The study was conducted in three phases. Firstly, a situational analysis was carried out to explore and describe the experiences and needs of the caregivers and the elderly. The situation analysis revealed themes in terms of interpersonal relationships that could be positive or negative regarding the elderly, with the sub-themes like communication, support and caring for elderly people. These themes and sub-themes include the following: Interpersonal relationships were viewed as an important aspect of the caring process. Lack of regular in-service training sessions for caregivers, with a subtheme of a lack of adequate knowledge of procedures. Lack of human resources, equipment and policies.In the second phase, a conceptual framework was derived from the results of phase 1, using the activities prescribed by Dickoff, James and Wiedenbach (1968). In the third phase, an educational programme was developed from of the findings of the previous phase. The Vicon project (2010) explains a programme as a plan of action for achieving something. The educational programme was implemented and evaluated and adjusted according to recommendations made. The feedback session with participants would indicate that their responses to the programme were positive, and they mentioned that the programme was indeed needed. The intention and hope are that the educational programme will help caregivers for the elderly to be competent and provide quality care.